Postoperative thrombotic thrombocytopenic purpura after aortofemoral bypass - Mainali, Naba R. (Co-Action Publishing, 2013)
Thrombotic thrombocytopenic purpura (TTP) is uncommon in the postoperative setting, even more so after vascular surgery. We present a case of thrombocytopenia after aortofemoral bypass, which highlights the importance of a high index of suspicion for postoperative TTP to avoid life-threatening consequences.